Cerebral Hemodynamics During a Cognitive-Motor Task Using the Limbs - Sagari, Akira; Kanao, Hiroyo; Mutai, Hitoshi; Iwanami, Jun; Sato, Masaaki; Kobayashi, Masayoshi (Frontiers in Human Neuroscience, 2020)
Abstract Background: Antagonistic tasks are cognitive-motor task trainings. Intervention programs involving antagonistic exercise tasks are being employed to help prevent falls and reduce the need for nursing care in older populations. Meanwhile, the effects of such tasks on blood flow in the brain remain obscure. This study aimed to clarify the effects of antagonistic tasks on prefrontal cortical cerebral haemodynamics. Materials and Methods: We assessed 13 healthy adults (2 men, 11 women; mean age, 21.4 ± 1.0 years). Participants imitated each of the antagonistic tasks presented on a PC monitor placed at a 120-mm viewing distance. All participants performed six tasks, consisting of upper limb tasks (non-antagonism, simple antagonism, and complex antagonism) and upper and lower limb tasks (tasks combining lower limb opening and closing movements with each upper limb task). We used near-infrared spectroscopy (NIRS) to measure cerebral blood flow dynamics, with oxygenated haemoglobin (Oxy-Hb) concentration changes as the main outcome. A 10-channel probe was placed on the participants’ forehead, focusing on the prefrontal cortex. We obtained a baseline NIRS measurement for 10 s, following which participants imitated the task presented on the PC monitor for 90 s. We measured the number of errors and the subjective difficulty of each task. Results: The increase in prefrontal cortex Oxy-Hb concentration was significantly greater in the complex antagonist conditions than in the non-antagonistic and simple antagonistic conditions. Conclusions: The study findings support that an increase in finger-shape complexity has a greater effect on cerebral blood flow dynamics in the prefrontal cortex than does an increase in the number of motor limbs involved in the task.